Badges and 'Sticks': Police Power Dynamics and African Agency in Nineteenth-Century Colonial Natal - Ivey, Jacob (The Journal of Natal and Zulu history, 2021)
In 1860, a case was brought before the court of Pietermaritzburg in the colony of Natal over the illegal possession and sale of guns. What made this case unique was the primary witness against the defendant: an African constable named Budaza. Budaza proudly claimed in his testimony that he had threatened the defendant with his 'sticks' during the arrest, despite the constable having misplaced his badge. Though Budaza appears only briefly in the colonial records, his testimony during the trial highlighted his firm belief in his position that transcended the badge he did not possess. Symbols of office like the badge and 'sticks' (likely a spear and knobkerrie) were signs of authority within the colonial community, but also representative of an internalised sense of power during this formative period of Natal. When these symbols of leadership and state power were implemented, they revealed a solidified sense of legitimacy granted by the colonial government but also embodied in the attitudes of African policemen. This article will use Budaza's case to help answer questions of police and colonial power and the notion of indigenous agency in the rural and urban segments of Natal. The interaction between Black police and white settler society will reveal the transitory nature of power in these police institutions and the complicated way these narratives are remembered within the history of KwaZulu-Natal.